2013
DOI: 10.1016/j.ijcard.2011.06.064
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged beneficial effect of bosentan treatment and 4-year survival rates in adult patients with pulmonary arterial hypertension associated with congenital heart disease

Abstract: Pulmonary arterial hypertension (PAH) associated with congenital heart disease (CHD) due to systemic to pulmonary shunting is associated with a high risk of morbidity and mortality. In this study we evaluated 4 years treatment effect of bosentan on exercise capacity and quality of life and survival rates in 64 adult patients with PAH associated with CHD, including patients with Down syndrome (DS). All patients were evaluated at baseline and during follow-up with laboratory tests, 6-minute walk test, quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 28 publications
5
45
1
3
Order By: Relevance
“…Subsequent observational studies confirmed the beneficial effect on symptoms and exercise capacity and, with a few exceptions [57,58], provided evidence that this symptomatic improvement is maintained mid-term. More recently, two studies have addressed the long-term impact of DTT in ES patients [59,60], confirming a sustained positive impact on WHO class and 6MWD in the long term. Improvement in quality of life has also been demonstrated [61].…”
Section: Eras and Pdesmentioning
confidence: 80%
“…Subsequent observational studies confirmed the beneficial effect on symptoms and exercise capacity and, with a few exceptions [57,58], provided evidence that this symptomatic improvement is maintained mid-term. More recently, two studies have addressed the long-term impact of DTT in ES patients [59,60], confirming a sustained positive impact on WHO class and 6MWD in the long term. Improvement in quality of life has also been demonstrated [61].…”
Section: Eras and Pdesmentioning
confidence: 80%
“…The BREATHE-5 (Bosentan Randomised Trial of Endothelin Antagonist-5) trial and its long-term open-label extension study demonstrated the benefit of bosentan in patients with Eisenmenger's syndrome in terms of significant improvements in exercise capacity, haemodynamics and functional class compared with placebo, independently of the location of the septal defect [42][43][44]. Data from a number of studies have since confirmed these benefits in the longer term in patients with PAH-CHD and specifically in patients with Eisenmenger's syndrome [45][46][47][48][49][50]. Importantly, treatment with bosentan has been shown not to reduce systemic arterial blood oxygen saturation over short- [42] and long-term treatment [47], demonstrating that it had no negative effect on the overall shunt.…”
Section: Management Of Pah-chd With Pah-specific Therapiesmentioning
confidence: 98%
“…Importantly, treatment with bosentan has been shown not to reduce systemic arterial blood oxygen saturation over short- [42] and long-term treatment [47], demonstrating that it had no negative effect on the overall shunt. Treatment with bosentan has also been shown to have a positive long-term effect on QoL, a particularly important consideration for Eisenmenger's syndrome patients [49]. Despite the lack of randomised controlled trials for other PAH-specific therapies, data are available from small, open-label studies; the earliest showing treatment benefit with epoprostenol [51].…”
Section: Management Of Pah-chd With Pah-specific Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This benefit is more robust in patients with PAH-CHD without Down syndrome. [118][119][120][121] The predominant adverse reaction of bosentan is increased hepatic transaminases, which can be seen up to w10% of patients. 105,116 However, the distinct benefit is that it is an oral agent and simple to administer.…”
Section: Specific Ph Therapeutic Optionsmentioning
confidence: 99%